Return to work after common mental disorders: a qualitative study exploring the expectations of the involved stakeholders - Scharf, Jessica; Angerer, Peter; Müting, Gesine Friederike; Loerbroks, Adrian (International journal of environmental research and public health, 2020)
Common mental disorders (CMDs) are risk factors for long-term sickness absence and unemployment. Therefore, return-to-work (RTW) processes have been introduced to facilitate the return of employees. As the success of RTW processes is considered to be determined by the cooperativeness of the involved stakeholders, we aimed to investigate the views of those stakeholders to disclose potentially diverging expectations. Qualitative interviews were conducted (08/2018-04/2019) among five stakeholder groups: returnees with a diagnosed CMD who were eligible for a RTW process; health care professionals nominated by the returnees; supervisors, colleagues and occupational physicians (the latter three groups were not nominated by the returnees). In total, 24 returnees, 13 health care professionals, 13 occupational physicians, 9 supervisors and 9 colleagues were interviewed (68 interviews in total). Potentially diverging expectations of the stakeholders related to whether diagnoses need to be disclosed by returnees. Agreement existed in terms of the need for a trustful relationship between employees and occupational physicians to initiate a RTW process early. As the understanding of all stakeholders’ viewpoints is one of the main factors promoting a successful RTW, we explored the expectations of those involved in the RTW process. One implication of our findings is to strengthen the role of occupational physicians, who could coordinate the return process.
Gesehen am 04.12.2025